2021
DOI: 10.1093/ndt/gfab027
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization of primary hyperoxaluria type 3 in comparison with types 1 and 2

Abstract: Background Primary hyperoxaluria (PH) type 3 (PH3) is caused by mutations in the hydroxy-oxo-glutarate aldolase 1 gene. PH3 patients often present with recurrent urinary stone disease in the first decade of life, but prior reports suggested PH3 may have a milder phenotype in adults. This study characterized clinical manifestations of PH3 across the decades of life in comparison with PH1 and PH2. Methods Clinical information w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 36 publications
1
37
1
3
Order By: Relevance
“…7,9 More than one-third of patients with PH2 progress to kidney failure by age 40 years. 14 More than half of PH3 cases (50% to 89%) present with renal stones before age 5 years, 15,16 14% to 29% develop chronic renal disease, [16][17][18] and 3% to 4% develop kidney failure by age 40 years. 8,16 Novel therapeutic strategies focus on ribonucleic acid interference (RNAi) to decrease the levels of enzymes involved in the glyoxylate metabolic pathway and so reduce oxalate production.…”
Section: Word Count = 3587mentioning
confidence: 99%
See 1 more Smart Citation
“…7,9 More than one-third of patients with PH2 progress to kidney failure by age 40 years. 14 More than half of PH3 cases (50% to 89%) present with renal stones before age 5 years, 15,16 14% to 29% develop chronic renal disease, [16][17][18] and 3% to 4% develop kidney failure by age 40 years. 8,16 Novel therapeutic strategies focus on ribonucleic acid interference (RNAi) to decrease the levels of enzymes involved in the glyoxylate metabolic pathway and so reduce oxalate production.…”
Section: Word Count = 3587mentioning
confidence: 99%
“…14 More than half of PH3 cases (50% to 89%) present with renal stones before age 5 years, 15,16 14% to 29% develop chronic renal disease, [16][17][18] and 3% to 4% develop kidney failure by age 40 years. 8,16 Novel therapeutic strategies focus on ribonucleic acid interference (RNAi) to decrease the levels of enzymes involved in the glyoxylate metabolic pathway and so reduce oxalate production. One such RNAi therapeutic, lumasiran (Alnylam Pharmaceuticals, Inc.), depletes an enzyme (hydroxyacid oxidase 1) responsible for glyoxylate synthesis.…”
Section: Word Count = 3587mentioning
confidence: 99%
“…PH type 2 (PH2) is caused by mutations in the gene glyoxylate reductase/hydroxypyruvate reductase ( GRHPR ), encoding the enzyme responsible for the reduction of glyoxylate to glycolate and hydroxypyruvate to D-glycerate. PH2 overall estimated frequency is 1:310,000 (carrier frequency 1:279) [ 3 ] and accounts for 10% of PH cases [ 13 ]. Most PH2-associated mutations produce an aberrant protein or affect catalytic activity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…HOGA1 is responsible for the conversion of 4-hydroxy-oxoglutarate to pyruvate and glyoxylate in mitochondria. PH3 accounts for 8–10% of PHs [ 13 ] and is characterized by recurrent nephrolithiasis, in some cases accompanied by hypercalciuria, that usually decreases with age [ 16 , 17 ]. Kidney function is preserved in most patients, although progressive impairment over decades is observed [ 13 ] and Martin-Higueras et al reported that 21.4% of patients had chronic kidney disease (CKD) stages 2 or higher [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation